Understanding the Pathophysiology of Intracranial Aneurysm: The ICAN Project. Issue 4 (16th March 2017) - Bourcier, Romain; Chatel, Stéphanie; Bourcereau, Emmanuelle; Jouan, Solène; Marec, Hervé Le; Daumas-Duport, Benjamin; Sevin-Allouet, Mathieu; Guillon, Benoit; Roualdes, Vincent; Riem, Tanguy; Isidor, Bertrand; Lebranchu, Pierre; et al.
Abstract: BACKGROUND: Understanding the pathophysiologic mechanism of intracranial aneurysm (IA) formation is a prerequisite to assess the potential risk of rupture. Nowadays, there are neither reliable biomarkers nor diagnostic tools to predict the formation or the evolution of IA. Increasing evidence suggests a genetic component of IA but genetics studies have failed to identify genetic variation causally related to IA. OBJECTIVE: To develop diagnostic and predictive tools for the risk of IA formation and rupture. METHODS: The French ICAN project is a noninterventional nationwide and multicentric research program. Each typical IA of bifurcation will be included. For familial forms, further IA screening will be applied among first-degree relatives. By accurate phenotype description with high-throughput genetic screening, we aim to identify new genes involved in IA. These potential genetic markers will be tested in large groups of patients. Any relevant pathway identified will be further explored in a large cohort of sporadic carriers of IA, which will be well documented with clinical, biological, and imaging data. EXPECTED OUTCOMES: Discovering genetic risk factors, better understanding the pathophysiology, and identifying molecular mechanisms responsible for IA formation will be essential bases for the development of biomarkers and identification of therapeutic targets. DISCUSSION: Our protocol has many assets. A nationwide recruitment allows for the inclusion of large pedigrees with familial forms of IA. It will combine accurate phenotyping and comprehensive imaging with high-throughput genetic screening. Last, it will enable exploiting metadata to explore new pathophysiological pathways of interest by crossing clinical, genetic, biological, and imaging information.